Sir2 paralogues cooperate to regulate virulence genes and antigenic variation in Plasmodium falciparum. - Christopher J Tonkin; Céline K Carret; Manoj T Duraisingh; Till S Voss; Stuart A Ralph; Mirja Hommel; Michael F Duffy; Liliana Mancio da Silva; Artur Scherf; Alasdair Ivens; Terence P Speed; James G Beeson; et al. (PLoS Biology)
Cytoadherance of Plasmodium falciparum-infected erythrocytes in the brain, organs and peripheral microvasculature is linked to morbidity and mortality associated with severe malaria. Parasite-derived P. falciparum Erythrocyte Membrane Protein 1 (PfEMP1) molecules displayed on the erythrocyte surface are responsible for cytoadherance and undergo antigenic variation in the course of an infection. Antigenic variation of PfEMP1 is achieved by in situ switching and mutually exclusive transcription of the var gene family, a process that is controlled by epigenetic mechanisms. Here we report characterisation of the P. falciparum silent information regulator's A and B (PfSir2A and PfSir2B) and their involvement in mutual exclusion and silencing of the var gene repertoire. Analysis of P. falciparum parasites lacking either PfSir2A or PfSir2B shows that these NAD(+)-dependent histone deacetylases are required for silencing of different var gene subsets classified by their conserved promoter type. We also demonstrate that in the absence of either of these molecules mutually exclusive expression of var genes breaks down. We show that var gene silencing originates within the promoter and PfSir2 paralogues are involved in cis spreading of silenced chromatin into adjacent regions. Furthermore, parasites lacking PfSir2A but not PfSir2B have considerably longer telomeric repeats, demonstrating a role for this molecule in telomeric end protection. This work highlights the pivotal but distinct role for both PfSir2 paralogues in epigenetic silencing of P. falciparum virulence genes and the control of pathogenicity of malaria infection.